Mental processes in professional football players - Grønset, Johan; Langagergaard, Martin; Sæther, Stig Arve (Frontiers in Psychology, 2024)
Objective: Clear connections have been found between mental processes and performance in elite level football. Yet, few studies have investigated how professional football players' experience the influence of mental processes on performance. Method: This study used a qualitative research design and in-depth interview of six Norwegian professional football players at elite level with a mean age of 28,3 years and represented five professional clubs. The aim of the study was to investigate how they perceived the importance of arousal regulation, mental toughness, and self-confidence, and that of the sport psychologist in developing these skills. Results: The results revealed a complex and multifaceted link between mental processes and performance. All players, demonstrate a conscious awareness of how mental processes influence their performance. The use of a sport psychologist in working with mental processes emerges as a crucial factor for developing their mental skills. Another important aspect is the need for increased knowledge about mental training's effect in elite football. Mental toughness emerges as the most significant mental process for players' performance because it makes them capable of coping with challenging situations and periods. Conclusion: This study shows that mental processes are important for performing, both related to arousal regulation, and self-confidence, and especially mental toughness. However, mental toughness was also considered a product of age and experience, where older players tend to have experience of more situations that enable them to handle adversity better than younger players. Interestingly, the youngest players seem to be most aware of the use of a sports psychologist.